2021
DOI: 10.3390/metabo11050301
|View full text |Cite
|
Sign up to set email alerts
|

A Low-Protein High-Fat Diet Leads to Loss of Body Weight and White Adipose Tissue Weight via Enhancing Energy Expenditure in Mice

Abstract: Obesity has become a worldwide health problem over the past three decades. During obesity, metabolic dysfunction of white adipose tissue (WAT) is a key factor increasing the risk of type 2 diabetes. A variety of diet approaches have been proposed for the prevention and treatment of obesity. The low-protein high-fat diet (LPHF) is a special kind of high-fat diet, characterized by the intake of a low amount of protein, while compared to typical high-fat diet, may induce weight loss and browning of WAT. Physical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 75 publications
3
6
0
Order By: Relevance
“…Simultaneously, LPD decreased the body weight of IR FKO and WT mice, consistent with previous studies 16, 21,29,34,35 . Since LPD reduces body weight in both genotypes and decreases glycemia only in IR FKO mice, we infer that the bene cial effects of LPD on glucose homeostasis are independent of body weight reduction in the IR FKO model.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Simultaneously, LPD decreased the body weight of IR FKO and WT mice, consistent with previous studies 16, 21,29,34,35 . Since LPD reduces body weight in both genotypes and decreases glycemia only in IR FKO mice, we infer that the bene cial effects of LPD on glucose homeostasis are independent of body weight reduction in the IR FKO model.…”
Section: Discussionsupporting
confidence: 92%
“…In the past decades, the alarming rise in the prevalence of metabolic diseases, including insulin resistance and diabetes, has invigorated interest in developing complementary therapeutic strategies. Reducing dietary proteins has recently been shown to promote or preserve metabolic health in young mice and rats 29,30,33 and obesity-induced metabolic dysfunction rodent models [34][35][36] . This study tested the therapeutic potential of protein restriction (LPD) on a diabetic lipodystrophic mouse model (adipose tissue-speci c insulin receptor knockout, IR FKO ) 22 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since dietary intervention can be well controlled in animals, additional studies, particularly in female populations, are warranted to provide definitive conclusions. Consistent with studies in humans [ 30 , 31 , 32 , 33 ] and male rodents [ 41 , 42 , 43 ], we found no benefit of a short-term KD on endurance exercise performance. Several key data may explain this observation.…”
Section: Discussionsupporting
confidence: 91%
“…Our review of the literature generally found that the KD was not an effective strategy to improve aerobic [ 30 , 31 , 32 , 33 ] or anaerobic [ 34 , 35 , 36 , 37 ] performance in human subjects. However, studies in rodent models were mixed, with observations of enhancements [ 38 , 39 , 40 ], impairments [ 26 ], and no change [ 41 , 42 , 43 ] in exercise performance. Studies in humans present certain limitations, such as controlling dietary intake and obtaining tissue for investigation and molecular insights.…”
Section: Discussionmentioning
confidence: 99%